Short-Term Effects of Gender-Affirming Hormone Therapy on Dysphoria and Quality of Life in Transgender Individuals: A Prospective Controlled Study - Foster Skewis, Lucas; Bretherton, Ingrid; Leemaqz, Shalem Y.; Zajac, Jeffrey D.; Cheung, Ada S. (Frontiers in Endocrinology, 2021)
BACKGROUND Gender affirming hormone therapy (GAHT), whilst considered the standard of care in clinical guidelines for the treatment of many transgender (trans) people is supported by low quality evidence. In this prospective longitudinal controlled study, we aimed to examine the effect of newly commencing GAHT on gender dysphoria and quality of life (QoL) over a 6 month period. METHODS Adult trans (including those with binary and/or non-binary identities) people newly commencing standard full-doses of masculinising (n=42; 35=trans masculine, 7=non-binary) or feminising (n=35; 33=trans feminine, 2=non-binary) GAHT and cisgender participants (n=53 male, n=50 female) were recruited to participate in this longitudinal prospective study. This analysis of gender dysphoria measured by the Gender Preoccupation and Stability Questionnaire and QoL measured by the RAND Short-Form 36 Health survey at baseline, 3 and 6 months after commencement of GAHT was a prespecified secondary outcome. Dysphoria and QoL over time in those starting GAHT compared to control comparison group matched for their presumed sex at birth is reported as the mean difference (95% confidence interval) adjusted for age. RESULTS In trans people initiating masculinising GAHT, there was a decrease in gender dysphoria with adjusted mean difference -6.80 (-8.68, -4.91), p<0.001, and a clinically significant improvement in emotional well-being (adjusted mean difference 7.48 (1.32, 13.64), p=0.018) and social functioning (adjusted mean difference 12.50 (2.84, 22.15), p=0.011) aspects of QoL over the first 6 months of treatment relative to cisgender female comparison group. No significant differences were observed in other QoL domains. In trans people initiating feminising GAHT, there was a decrease in gender dysphoria (adjusted mean difference -4.22 (-6.21, -2.24), p<0.001) but no differences in any aspects of QoL were observed. CONCLUSIONS In the short-term, our findings support the benefit of initiating masculinising or feminising GAHT for gender dysphoria. Masculinising GAHT improves emotional well-being and social functioning within 6 months of treatment. Multidisciplinary input with speech pathology and surgery to support trans people seeking feminisation is likely needed. Further longitudinal studies controlled for other confounders (such as the presence of social supports) contributing to QoL are needed.